‘Who wants to be a teacher in Ghana?’ A structural equation modelling analysis of prospective language teachers’ behavioural intentions to pursue a career in teaching - Ernest Nyamekye; John Zengulaaru (PLoS ONE, 2025)
Despite its significant role in the development of society, the teaching profession is arguably one of the least preferred professions in Ghana. It has been argued that the declining interest in the teaching profession is partly contingent on the deteriorated conditions of service and the unfavourable reputation it has earned in Ghana in contemporary times. Amid these concerns, we were compelled to investigate prospective language teachers’ behavioural intention to pursue a career in teaching. Using Ajzen’s theory of planned behaviour, 111 prospective language teachers in two higher educational institutions in Ghana were engaged in this inquiry. The study’s results, obtained through a partial least squares structural equation modelling analysis, indicated that prospective language teachers’ behavioural beliefs, control beliefs, and subjective norms significantly influenced their intention to pursue a teaching career (R2 = 56.1%). We, thus, recommend that the Ministry of Education should consider addressing teachers’ working conditions and launching public awareness campaigns to enhance the perception of teaching’s importance. By improving teachers’ professional identity, policymakers, particularly the Ghana Education Service, can attract prospective teachers and instill a positive view of teaching as an ideal profession for the youth.